Making social sciences more scientific: Literature review by structured data - Vuong Quan-Hoang (MethodsX, 2020)
The paper proposes a new method for conducting a literature review by structured data of more than 2200 scientific articles and 1300 researchers on SSHPA (Social Sciences and Humanities Peer Awards), an open database of Vietnamese social scientists’ scientific productivity. Based on the logical structure of SSHPA, the authors create a specialized database for the literature review: SDA (SSHPA Data Analysis). Combining expert's caliber and computational algorithms, SDA is expected to offer an immensely efficient and analytical based method of scanning data, hence ameliorating the traditional approach to conducting a literature review. • A specialized database for literature review is created using the scientific articles and author profiles from SSHPA, an open database of Vietnamese social scientists’ productivity. • The review database assigns values of topics or methodological attributes to articles sourced from SSHPA. • Then, the authors can query comprehensive data tables, graphs, or diagrams to use for literature review.